Seguridad informática y métodos de protección en infraestructuras tecnológicas y su incidencia en la intranet de la Universidad Técnica de Babahoyo, año 2015. Diseño de una infraestructura tecnológica segura - Vega Villacis, Geovanny Eduardo (2015)
Today, for most companies, institutions or any organization, the most important thing to consider is the information resource. Not far away this reality, living the Technical University of Babahoyo that it has an intranet where most activities take place and information is generated legal, administrative, academic, etc. Why this research raises the following problem to solve: How adequate topology affects the design of secure technological infrastructure and protection methods at the Technical University of Babahoyo? To address this issue, it has set several objectives of study: Identify the levels of vulnerability and threats that displays the intranet, properly use paradigms in information security, such as defense in depth model to statistically determine the irregularities, and finally make a safe design for the intranet of the Technical University of Babahoyo infrastructure. The methods and research techniques used were: Inductive-deductive and hypothetical-deductive, analytic-synthetic that allowed evaluate the research objectives and validate the following hypothesis: "The security system and infrastructure protection methods technology, favorable impact on the intranet of the Technical University of Babahoyo." The results obtained through surveys and interviews with users, administrators, teachers and authorities of the institution demonstrated that there is a 77% error in the network and services, such as Internet access registered level security hardware, software and interconnectivity users. Finally it obtained as proposed a design that will improve securities within the university network, will allow the implementation of a captive portal to ensure the entry only registered staff intranet, account creation encrypted user, securing the network against attacks malwares and viruses with network monitoring; with the use of Open Source Zentyal Linux system Ubuntu.